Pengukuran Kinerja Karyawan Dengan Metode Human Resource Scorecard (HRSC) Dan Total Quality Management (TQM) Pada PT. XYZ - Dinna Nur Fadilah; Febrina Agusti; Fery Wisnu Saputro (Politeknik Kampar, 2023)
The development of the industrial world which is increasingly rapid at this time requires a company to pay attention to the smooth production process and employee performance. PT. XYZ is a manufacturing company engaged in the garment sector. Performance measurement that is still applied to PT. XYZ is still using a target and attendance system, therefore the performance measurement is still not able to describe the employee's contribution to the company. The purpose of this study is to measure the performance of production employees, especially the sewing department line 2 and 3 using the Human Resource Scorecard (HRSC) and Total Quality Management (TQM) methods. Collecting data through interviews and distributing questionnaires to employees. Test results for the validity and reliability of the questionnaire data in this study obtained an Rtable of 0.254. The alpha value for the HRSC method is 0.602 and the alpha value for the TQM method is 0.807. The results of data processing on 4 HRSC perspectives, namely the financial perspective of 203 (satisfactory), the customer perspective of 695 (satisfactory), the internal business process perspective (satisfactory), and the growth and learning perspective of 364 (satisfactory) and the results of the TQM method are 1723 ( satisfying)